2011
DOI: 10.1111/j.1468-1331.2011.03439.x
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrotendinous xanthomatosis in Spain: clinical, prognostic, and genetic survey

Abstract: This is the first nationwide extensive series of CTX reported in Spain. The higher number of cases in some areas suggests a possible founder effect. Spinal forms had a less severe prognosis. A delayed diagnosis could contribute to the lack of significant response to treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
101
1
16

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 120 publications
(120 citation statements)
references
References 24 publications
0
101
1
16
Order By: Relevance
“…A genetic epidemiology study using the Exome Aggregation Consortium (ExAC) cohort of~60,000 unrelated adults from global populations evaluated the allele frequency of 57 known and 29 predicted CTXcausing variants and found that estimated incidence of CTX was highest in South Asians and East Asians, followed by North Americans, Europeans, and Africans (Appadurai et al 2015) (Table 1). Prevalence estimates vary considerably among different populations, with a particularly high prevalence reported for Jews of Moroccan origin and Druze in Israel (Table 1) (Berginer and Abeliovich 1981;Lorincz et al 2005;Pilo-de-la-Fuente et al 2011). Consistent with this, high CTX gene carrier frequencies have been reported for these populations (Berginer and Abeliovich 1981;Rosner et al 2009;Falik-Zaccai et al 2008) (Table 1).…”
Section: Epidemiologymentioning
confidence: 79%
See 4 more Smart Citations
“…A genetic epidemiology study using the Exome Aggregation Consortium (ExAC) cohort of~60,000 unrelated adults from global populations evaluated the allele frequency of 57 known and 29 predicted CTXcausing variants and found that estimated incidence of CTX was highest in South Asians and East Asians, followed by North Americans, Europeans, and Africans (Appadurai et al 2015) (Table 1). Prevalence estimates vary considerably among different populations, with a particularly high prevalence reported for Jews of Moroccan origin and Druze in Israel (Table 1) (Berginer and Abeliovich 1981;Lorincz et al 2005;Pilo-de-la-Fuente et al 2011). Consistent with this, high CTX gene carrier frequencies have been reported for these populations (Berginer and Abeliovich 1981;Rosner et al 2009;Falik-Zaccai et al 2008) (Table 1).…”
Section: Epidemiologymentioning
confidence: 79%
“…Currently available animal models for CTX (e.g., cyp27a1 knockout mouse models) are suboptimal, as they do not demonstrate clear and consistent accumulation of cholestanol and/or bile alcohols or neurologic signs and symptoms associated with CTX (DeBarber et al 2011;Rosen et al 1998); poor genotype-phenotype correlation in CTX (Verrips et al 2000a;Pilo-de-la-Fuente et al 2011) also limits the ability to extrapolate from animal models. Studies that attempted to duplicate the CTX phenotype by feeding animals cholestanol-enriched diets found increased cholestanol levels in various tissues but not the brain (Berginer et al 2015); such findings suggest that cholestanol does not efficiently pass the intact blood-brain barrier (BBB).…”
Section: Etiologymentioning
confidence: 99%
See 3 more Smart Citations